SUPERVISOR KEPALA SEKOLAH DALAM MEWUJUDKAN PARTISIPASI GURU PPKn DI SMP NEGERI 2 KOTA TERNATE - Leko, Tati; Kamisi, Mohtar; Abbas, Irwan (Universitas Khairun, 2023)
The research objectives to be achieved are (1) to find out the leadership of the principal as a supervisor in realizing the participation of Civics teachers and students in SMP Negeri 2 Kota Ternate, (2) To find out what factors support and hinder the leadership of the principal in realizing participation of Civics teachers at SMP Negeri 2 Kota Ternate. The method used in this research is descriptive qualitative research method. The data sources in this study were school principals and civic education teachers at SMP Negeri 2 Kota Ternate. The analysis technique used in this research is using qualitative analysis method.Based on data analysis and conclusions, it can be seen (1) the implementation of the supervision of the principal at SMP Negeri 2 Kota Ternate is classified as very good, because in the implementation of the supervision of the principal, the first thing he did was to make a plan regarding the steps that must be carried out in supervising, the second was to carry out classroom supervision during the learning process takes place, the third is to carry out an approximate analysis of what needs to be improved. In addition, the principal carries out supervision at the beginning of each semester. The role of the principal as a supervisor in realizing the participation of Civics teachers at SMP Negeri 2 Kota Ternate first, the principal acts as a motivator, namely being able to provide motivation in the form of directions to teachers so as to create professional educators. Then as a facilitator, namely the principal is able to provide facilities that will facilitate teaching and learning activities so as to create a pleasant learning environment,(2) supporting factors for the principal in increasing teacher participation in SMP Negeri 2 Ternate City are the creation of a conducive atmosphere and a sense of security at school, communication which is well established between school members, as well as the provision of rewards for teachers who excel and can also be used as motivation for other teachers. The existence of an award given by the principal will affect the morale of the teacher to be more active and maintain good performance. Meanwhile, the inhibiting factor for school principals in realizing teacher participation is the existence of teachers who have a character that is less sociable, feels inferior, lacks motivation, and lacks discipline;Â Key Words: Principal, Supervisor, Teacher Participation.